2010
DOI: 10.3944/aott.2010.2233
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the medial longitudinal arch: a comparison between the dynamic plantar pressure measurement system and radiographic analysis

Abstract: The arch index method is a simple and reproducible pedobarographic measurement for the evaluation of the MLA. However, the angles measured on statically obtained radiographs and showing correlations with the arch index may give similar results concerning the MLA. Both static and dynamic methods can be utilized in the evaluation of the MLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 19 publications
0
38
1
1
Order By: Relevance
“…Pe do ba ro gra fia jest szcze gól nie przy datna w przed ope ra cyj nym pla no wa niu le cze nia i po ope racyj nej je go oce nie. Mo że ona rów nież słu żyć, wraz z trój wy mia ro wą ana li zą cho du i elek tro mio gra fią, ocenie go je nia się zła ma nia [31], bądź też sa mo dziel nie lub z ba da niem ra dio lo gicz nym, czy za po mo cą me to dy arch in dex, oce nie łu ku po dłu żne go sto py [32].…”
Section: Lor Kow Ski J Et Al Pedobarography -A Methods Of Foot and Aunclassified
“…Pe do ba ro gra fia jest szcze gól nie przy datna w przed ope ra cyj nym pla no wa niu le cze nia i po ope racyj nej je go oce nie. Mo że ona rów nież słu żyć, wraz z trój wy mia ro wą ana li zą cho du i elek tro mio gra fią, ocenie go je nia się zła ma nia [31], bądź też sa mo dziel nie lub z ba da niem ra dio lo gicz nym, czy za po mo cą me to dy arch in dex, oce nie łu ku po dłu żne go sto py [32].…”
Section: Lor Kow Ski J Et Al Pedobarography -A Methods Of Foot and Aunclassified
“…Although there are many studies comparing the radiological measures for diagnosing flatfoot (8,(13)(14)(15), there is no consensus on the radiologic evaluation of the MLA. While Younger et al (14) reported that the TFMA was an accurate radiographic identifier, Sensiba et al (15) suggested that CPA had a higher interobserver reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Surface area measurement of irregularly shaped structures by a point-counting method was described as an efficient approach for obtaining the required cut surface areas of the structure (8). The PAL method was previously suggested as an alternative to the Cobb method for the radiographic evaluation of the degree of lumbar lordosis when ImageJ's estimation was accepted as the gold standard (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pes cavus is characterised by an abnormally high-arched foot with an inverted calcaneus. Evidently, the medial arch is the main point of reference in diagnosis of pes planus or pes cavus [32], although the morphology of both lateral and transverse arches may also provide valuable information in the diagnosis of these deformities.…”
Section: Introductionmentioning
confidence: 99%